Infectivity of malaria vector mosquitoes: correlation of positivity between ELISA and PCR-ELISA tests - P?voa, Marinete Marins (2016)
Minist?rio da Sa?de. Funda??o Nacional de Sa?de. Instituto Evandro Chagas. Bel?m, PA, Brasil.